Geographic distribution of tropical cacomixtle (Bassariscus sumichrasti) in Puebla, México - Pozos-López, Luis Ángel; González-Ruiz, Noé; Ramírez-Pulido, José (Therya Notes, 2024)
The tropical cacomixtle (Bassariscus sumichrasti) is a rare neotropical carnivore with a geographic distribution restricted to the southern tropical part of the México and Central America. There have been 2 records of this species in the state of Puebla, specifically in the vicinity of Tehuitzingo and Acatlán. During a routine assessment of the Mammal Collection at the Universidad Autónoma Metropolitana, we found a specimen with the characteristics of B. sumichrasti. The specimen was collected near Zacapala, in the southwestern extreme of Puebla in a tropical deciduous forest. Our specimen along with previous records of B. sumichrasti in Puebla, are concentrated in the northern part of the Balsas Basin, where sympatry with B. astutus is possible. Given the limited available information on the species, this new specimen is a valuable addition to the knowledge of the distribution that can contribute to a better understanding of the species.